An Analysis of the Effectiveness of Listening Activities in Improving English Learning/Reading (L2 Language-English) - Hsu Yen Hui (SHS Web of Conferences)
This study delves into the important role of listening activities in improving the effectiveness of English listening learning, covering multiple aspects such as the design, implementation, interaction, evaluation, and feedback of classroom and home listening activities at different stages from primary school to high school. The study points out that listening plays a core role in language learning and significantly improves students’ oral, reading, and writing abilities. By designing diverse listening activities and achieving effective teacher-student and student-student interaction and cooperation, students’ English listening proficiency can be significantly enhanced, promoting the comprehensive development of their language abilities. At the same time, the study also emphasized the crucial role of evaluation and feedback in listening teaching, advocating that teachers should develop scientific and reasonable evaluation standards based on students’ age characteristics and cognitive levels and provide students with timely, specific, and targeted feedback. We believe that in the future, with the continuous updating of educational technology and teaching concepts, the positive role of listening input in improving students’ reading ability will be more widely recognized and applied, helping students achieve a leap in reading ability and further promoting the comprehensive improvement of English teaching quality.